Representasi Tambatan Media Sosial Akun Instagram @jrxsid “IDI Kacung WHO” (Analisis Wacana Kritis Norman Fairclough) - Muharam, Muhammad Rizky; Dharta, Firdaus Yuni; Santoso, Made Panji Teguh (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research was compiled by Miuhammad Rizky Muharam, a student of the Communication Studies Program, Faculty of Social and Political Sciences, Singaperbangsa University Karawang with the title "Representation of Social Media Moorings for Instagram Account @JRXSID 'IDI KACUNG WHO' (Critical Discourse Analysis Norman Fairclough)". The researcher uses Norman Fairclough's Critical Discourse Analysis which sees language as a tool of power practice. Fairclough argues how text can be related from a micro to a macro perspective. By using three basic elements that become the material for analysis, the researcher sees the object of research in which the researcher analyzes the mooring of the Instagram account @jrxsid regarding "IDI Kacung WHO" which became a public conversation so that it became a controversial post. So that in the study the results were found in the form of the post representing a social criticism where the @jrxsid account owner posted a post with inappropriate language and also varied opinions ranging from comments from the post and also the results of interviews from informants, and social factors also have The impact is to support the opinion of the mooring @jrxsid regarding the " IDI Kacung WHO ".